KORELASI ASPEK IBU TERHADAP INISIASI MENYUSU DINI - Nordianiwati, Nordianiwati; Susanti, Ni Made Dewi; Herlina, Herlina; Kristina, Yunita (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Based on preliminary studies conducted at RSUD Sheikh Yusuf, data related to the implementation of Early Breastfeeding Initiation (IMD) shows a significant number. In 2022, the number of mothers who gave birth at the hospital was recorded at 1,541 people, and of these, 1,264 mothers successfully underwent IMD. This indicates a fairly high rate of IMD implementation in that year. However, in September 2023, although the number of mothers who gave birth was recorded at 82 people, only 66 mothers were able to carry out IMD. The purpose of the study was to determine the correlation between maternal aspects and early breastfeeding initiation. The research design used in this study was Cross Sectional. The research was conducted at Sheikh Yusuf Hospital. The research was conducted in December 2023. The population was all new mothers who gave birth at Sheikh Yusuf Hospital in November 2023 as many as 64 people. The sample amounted to 64 people using Total Sampling. The research instrument used a research questionnaire. Data analysis was performed univariate and bivariate. The results showed a relationship between maternal knowledge (p value: 0.038) and maternal health status (p value: 0.029) on Early Breastfeeding Initiation. It is recommended that the hospital can carry out monitoring and evaluation activities and appoint a person in charge of monitoring the implementation of Early Breastfeeding Initiation (IMD) so that it can be carried out properly.Keywords: Early Breastfeeding Initiation, Maternal Knowledge, Maternal Health Status